2020
DOI: 10.3126/jpahs.v7i3.33824
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasound imaging with histopathological findings in gestational trophoblastic disease

Abstract: Introduction: Gestational trophoblastic diseases include a spectrum of pregnancy-related diseases caused by abnormal proliferation of the placenta.  The main aim of this study was to correlate ultrasound imaging with histopathological findings. Method: This is the retrospective chart review of findings of transabdominal ultrasonography in clinically suspected gestational trophoblastic diseases which were confirmed by histopathology after the evacuation of a product of conception during 3 years from 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…4 Likewise, in a study conducted by Jaiswal P et al, out of 141 cases, 110 (71.0%) were partial mole, 15(9.7%) complete mole, 12(7.7%) invasive mole, three (1.9%) persistent mole and one (0.6%) choriocarcinoma. 10 The mean age of presentation in this study was 25.4 years which was in concordance with other studies by Jagtap SV et al and Veeraraghavan G et alwith 24.5, and 23.5 years respectively. 2,5 However, a study conducted by Koirala A et al showed a mean age of 22 years.…”
Section: Discussionsupporting
confidence: 92%
“…4 Likewise, in a study conducted by Jaiswal P et al, out of 141 cases, 110 (71.0%) were partial mole, 15(9.7%) complete mole, 12(7.7%) invasive mole, three (1.9%) persistent mole and one (0.6%) choriocarcinoma. 10 The mean age of presentation in this study was 25.4 years which was in concordance with other studies by Jagtap SV et al and Veeraraghavan G et alwith 24.5, and 23.5 years respectively. 2,5 However, a study conducted by Koirala A et al showed a mean age of 22 years.…”
Section: Discussionsupporting
confidence: 92%